Utilizing Noice App for Students Listening Skill - Mutiara Ramadhani; Muhamad Sofian Hadi (English Language in Focus (ELIF), 2022)
The amount of capacity to learn a language varies from student to student. A student's ability can develop if they are exposed to appropriate and enjoyable learning techniques for improving their learning abilities. Therefore, the purpose of this research is aimed that using Podcast in Noice application can improve English learning process using the listening method. This research was conducted from May 10 until May 30 2023 at SMPN 6 South Tangerang. The method used in this research is a quantitative method with an experimental design that applied control class techniques. In collected data, the researcher used test as an instrument. Data collection was analyzed statistical use t-test formula. The results of the post-test were 81.15 compared to the pre-test were 64.23. Based on statistical analysis, the result of H1 was accepted and H0 was rejected. So, for the hypothesis H1 was accepted it can be concluded that using Podcast in Noice application is effective technique to improve students listening skill mastery.